Bahasa Inggris - Syva Lestiyani Dewi; Dede Trie Kurniawan; Rendi Restiana Sukardi (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this study was to examine common misconceptions among elementary school students regarding the greenhouse effect. The method used was descriptive research, using 52 student samples selected by purposive sampling technique, and the Rasch model was used to analyze the data. The results showed that the Rasch Model confirmed the validity of the tool, highlighting the challenges in understanding the concept of the greenhouse effect among bright students. Students had a misconception rate of 63% when analyzing the relationship between the ozone layer and the greenhouse effect, 62% when distinguishing between the greenhouse effect and global warming, 60% when examining the relationship between the greenhouse effect and cow dung waste, and 56% when determining the relationship between the greenhouse effect and acid rain. Effective teaching strategies are essential for correcting misconceptions, and future research should explore media or learning models to address these issues. It is imperative for educators to design targeted interventions that specifically target these prevalent misconceptions to improve science education outcomes among elementary school students in Indonesia.